2008
DOI: 10.1142/s012962640800348x
|View full text |Cite
|
Sign up to set email alerts
|

EDGeS: THE COMMON BOUNDARY BETWEEN SERVICE AND DESKTOP GRIDS

Abstract: Service grids and desktop grids are both promoted by their supportive communities as great solutions for solving the available compute power problem and helping to balance loads across network systems. Little work, however, has been undertaken to blend these two technologies together. In this paper we introduce a new EU project, that is building technological bridges to facilitate service and desktop grid interoperability. We provide a taxonomy and background into service grids, such as EGEE and desktop grids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Experimental Setup SETI@home [15] has been selected for resources and LCG1 [16,17] dataset has been used for jobs submitted to be scheduled on volunteer resources. SETI@home project has recorded activities of 60883 nodes for a period of 10 months [15].…”
Section: Results and Simulationmentioning
confidence: 99%
“…Experimental Setup SETI@home [15] has been selected for resources and LCG1 [16,17] dataset has been used for jobs submitted to be scheduled on volunteer resources. SETI@home project has recorded activities of 60883 nodes for a period of 10 months [15].…”
Section: Results and Simulationmentioning
confidence: 99%
“…read the description file of the workunit produced by the jobwrapper client, 2. create an input package out of the workunit's input files. This input package contains every file that is required to run the workunit on a stand-alone machine, 3. create a JDL file and a wrapper script using the information in the description file.…”
Section: First Version Of the Boinc → Egee Bridgementioning
confidence: 99%
“…The European EDGeS project [3] aims at establishing an integrated SG-DG infrastructure where the DG → SG bridge enables desktop grids to submit task units as jobs into the service grids and the SG → DG bridge ensures the job movement into the opposite direction. In this paper, we describe research on how such DG → SG and SG → DG bridge can be created for BOINC and EGEE.…”
Section: Introductionmentioning
confidence: 99%
“…An example for the former one is Globus that enables the interconnection of Condor pools. The EDGeS technology [5] enables the interconnection of BOINC, XtremWeb and SZDG systems. However, here we focus on the internal facilities of the DG systems.…”
Section: Interconnection/scalabilitymentioning
confidence: 99%
“…Currently DC API is implemented for BOINC, Condor and XtremWeb [4]. Within the EDGeS [5] project we demonstrated that applications originally developed by DC API for SZDG could run without any modification on the XtremWeb platform. Within a Hungarian Grid project [6] we showed that SZDG applications written with DC API could run on the Hungarian ClusterGrid [7] that is a Condor based Grid system.…”
Section: Introductionmentioning
confidence: 96%